Tonga : Statistical Appendix. (IMF Staff Country Reports; Country Report, 2006)
The statistical data on real gross domestic product, agricultural products, indicators of economic activity, consumer price index, population and labor market of Tonga has been detailed. The data on central government revenue, and current expenditure, national debt, Tonga trust fund, public sector enterprises, monetary survey, accounts of the national reserve bank, bank credit by sector, accounts of the Tonga development bank, interest rate structure, exports by major commodity, imports by commodity, category, and sector, external debt and debt service, and related economic indices have been presented.